EFEKTIFITAS TEKNIK RELAKSASI OTOT PROGRESIF DAN RELAKSASI AUTOGENIK TERHADAP TINGKAT NYERI PADA PASIEN POST OPERASI SEKSIO CAESAREA DI RUANG CEMPAKA RSUD NGUDI WALUYO - Septyani Nevy Mega Nurastam; rony yuliwar; susi milwati (Poltekkes Kemenkes Malang, 2019)
Abstract: The mostly problem during post surgery is pain accompanied by the appearance of physiological response in the form of peripheral vasoconstriction. One of the nursing self-care actions for non-pharmacological pain management is progresive muscle relaxation, autogenic relaxation. This study aims to determine the differences of pain level before and after progresive muscle relaxation, autogenic relaxation in patients which is Sectio Caesarea surgery at RSUD Ngudi Waluyo Wlingi. This research has been done ethical clearance test before result test. This study used quasy-experiment with two group pre test and post test design approaching. It sample were 34 people which devide in two group using purposive sampling technique. This study used paired t-test and independent t-test. The results showed the level of pain before progressive muscle relaxation was 6.00 and after progressive muscle relaxation to 1.65 whereas the pain level before autogenic relaxation was 6.53 and after autogenic relaxation to 2.25. The result of paired t-test statistic shows there are significant differences before and after progresive muscle relaxation, autogenic relaxation of pain level with p is 0.000 and the result of independent t-test statistic shows there are a significant decrease in the level of pain after progressive muscle relaxation annd autogenic relaxation with p = 0,017. Thus progressive muscle relaxation therapy and autogenic relaxation therapy can be a reference and nursing intervention in the treatment of postoperative patients, especially section caesarea. However, progresive muscle relaxation is more higher in lowering pain level than autogenic relaxation.